The use of gross efficiency coefficients in cyclists` endurance tests - Borkowski, J.; Sodolska, D.; Hebisz, R.; Zaton M. (Central European Journal of Sport Sciences and Medicine, 2015)
The efficiency of energy conversion of aerobic metabolism to external work is of great importance to sports exercise. Despitethis fact, gross efficiency (GE) is not commonly used as a parameter in the assessment of cyclists` exercise ability. It is also known that road cyclists traverse most of their route at a work intensity below the anaerobic threshold (AT). We tried to examine the relationship between the standard aerobic parameters used for defining the endurance of cyclists and GE, measured just below the anaerobic threshold. Fifty cyclists were subjected to a progressive test. Work done and the basic respiratory and circulatory parameters were measured. Gross efficiency was calculated at work intensity just below AT. We observed a very low correlation (R = -0.137) between GE (24.9 ±2.06) and maximal oxygen uptake (VO2max) - 63.8 ±6,27 ml × kg-1 × min- 1. The strongest correlation (R = -0.258) was recorded between GE and the percentage of maximal oxygen consumption (58.9 ±7.0%) for the load prior to the occurrence of the anaerobic threshold. The weak, but existing correlation between GE and selected respiratory and circulatory parameters may suggest that GE provides unique and independent information about the examined athletes.